Doped Sc2C(OH)2 MXene: new type s-pd band inversion topological insulator. (21st March 2018) - Balcı, Erdem; Akkuş, Ünal Özden; Berber, Savas
Abstract: The electronic structures of Si and Ge substitutionally doped Sc2 C(OH)2 MXene monolayers are investigated in density functional theory. The doped systems exhibit band inversion, and are found to be topological invariants in Z 2 theory. The inclusion of spin orbit coupling results in band gap openings. Our results point out that the Si and Ge doped Sc2 C(OH)2 MXene monolayers are topological insulators. The band inversion is observed to have a new mechanism that involves s and pd states.